2021
DOI: 10.1093/hmg/ddab171
|View full text |Cite
|
Sign up to set email alerts
|

Loss of DRC1 function leads to multiple morphological abnormalities of the sperm flagella and male infertility in human and mouse

Abstract: Motile cilia and flagellar defects can result in primary ciliary dyskinesia (PCD), which is a multisystemic genetic disorder that affects roughly 1:10000 individuals. The nexin-dynein regulatory complex (N-DRC) links neighboring doublet microtubules within flagella, serving as a central regulatory hub for motility in Chlamydomonas. Herein, we identified two homozygous DRC1 variants in human patients that were associated with multiple morphological abnormalities of the sperm flagella (MMAF) and male infertility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 60 publications
3
26
1
Order By: Relevance
“…For example, the expression of DRC2, LRRC48 (DRC3), and GAS8 (DRC4) is reduced in DRC1 mutant mice. 83 The expression of DRC1, DRC3, DRC5, and DRC11 is reduced in Chlamydomonas DRC2 mutant. 92 Similarly, DRC7 interacts with DRC3, GAS8 (DRC4), and TCTE1 (DRC5), and the expression of those proteins are decreased in Drc7 –KO spermatozoa.…”
Section: Proteins Compose the Axonemal Structurementioning
confidence: 96%
See 1 more Smart Citation
“…For example, the expression of DRC2, LRRC48 (DRC3), and GAS8 (DRC4) is reduced in DRC1 mutant mice. 83 The expression of DRC1, DRC3, DRC5, and DRC11 is reduced in Chlamydomonas DRC2 mutant. 92 Similarly, DRC7 interacts with DRC3, GAS8 (DRC4), and TCTE1 (DRC5), and the expression of those proteins are decreased in Drc7 –KO spermatozoa.…”
Section: Proteins Compose the Axonemal Structurementioning
confidence: 96%
“…In the past few years, there has been rapid progress in the functional analysis of N‐DRC genes. Deletion or mutation of Drc1 , 83 Lrrc48 ( Drc3 ), 84 Tcte1 ( Drc5 ), 85 Drc7, 86 and Iqcg ( Drc9 ) 87 has been shown to cause male infertility in mice. Additionally, mutation of DRC1 , 83 CCDC65 ( DRC2 ), 88 , 89 and GAS8 ( DRC4 ) 90 was found to be associated with PCD in humans.…”
Section: Proteins Compose the Axonemal Structurementioning
confidence: 99%
“…Gene CIB4 knockout (KO) mice are sterile because haploid differentiation becomes impaired ( 33 ). Knocking out the DRC1 gene in mice completely disorders the axoneme structure of sperm flagella, impairing sperm motility ( 34 ). Research in bulls shows that HADHA proteins are significantly more abundant in the immotile sperm of low-fertility males than in the sperm from high-fertility males ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…DRC1 is a key component of the nexin-dynein regulatory complex (N-DRC) and plays an important role in ciliary movement ( 25 ). Previous studies have reported that mutations in DRC1 largely result in primary ciliary dyskinesia ( 26 , 27 ), morphological abnormalities of the sperm flagella, and male infertility ( 28 ). Notably, a study revealed the central role of cilium and cilia transduced-cell signaling in the pathogenesis of CHD by the recessive forward genetic screen in mice.…”
Section: Discussionmentioning
confidence: 99%